Modeling and parametric study ofsolid oxide fuel cell performance - Mohamed Mankour; M’hamed Sekour (Institute of Advanced Engineering and Science, 2022)
Renewable energies are in the news these days and are seen as a solution to endorse energy independence and diminish greenhouse releases. One possible new renewable source that is emerging as a promising technology is the fuel cell. The ‘F.C’ is an electrochemical system that transfers the chemical power of a redox response into electrical energy with simultaneous production of water and heat. In fact, there are numerous kinds of fuel cells; in our work we are interested in studying the solid oxide fuel cellSOFC. In the context of this work, a modeling tool has been implemented SOFCs to the analogy between the electrical, thermal and chemical domains; this way of proceeding constitutes a simple, evolutionary and efficient tool. Using this modeling, a simulation was carried out in order to obtain the dissimilar characteristics and the impact of the studied parameters on the performance of the SOFC fuel cell.